Iklim Kerohanian Kampus Sebagai Prediktor Perkembangan Performa Kerohanian Mahasiswa - Budi Harwanto (Jurnal Ilmiah Wahana Pendidikan, 2022)
Spirituality campus climate and spiritual performance have been a large amount of research study in recent years. Research has found that spirituality campus climate is one of the most significant contributors to students’ spiritual performance. However, there is only a little research done on the link between these two variables in the context of Adventist tertiary level of Indonesia. This article explored the influence of the spirituality campus climate to students’ spiritual performance. A total of 244 students of Universitas Klabat participated in this study. The findings showed that: (1) using Pearson’s correlation, all dimensions of spirituality campus climate (campus spirituality programs, religion class, and teachers’ spirituality performance) and students’ spiritual performance had a positive and significant relationship (r = .485, p < .001) , and (2) using multiple regression analysis, all dimensions of spirituality campus climate help predict 32,1% of the total variance of students’ spiritual performance.